Changes in Organic Carbon, NO3-N, Electrical Conductivity Values and Soil Respiration Along a Soil Depth Due to Surface Application of Organic Wastes - DEMIR, ZEYNEP; GULSER, COSKUN (Asian Journal of Chemistry, 2010)
Changes in some chemical properties along a clay loam soil depth due to application of hazelnut husk, tea and tobacco wastes to soil surface were investigated under greenhouse conditions. At the end of 20, 40 and 80 d of incubation, changes in organic carbon, total nitrogen, soil respiration (CO2 production), NO3-N, pH, EC were determined in 10, 20, 30, 40 and 50 cm depth of the clay loam soil. While organic carbon in 0 to 20 cm soil depth decreased after 20 d, organic carbon in 30 to 50 cm soil depth increased between 40 and 80 d for all organic waste treatments. Except control treatment, organic carbon leached from soil surface (0-20 cm) to deeper soil layers (30-50 cm) of organic waste treatments between 40 and 80 days. Soil respiration significantly increased near the surface soil layers of organic waste treatments compared with the control. Organic carbon contents along soil depth generally increased with control (C) < tobacco wastes < hazelnut husk < tea applications. NO3-N values in all soil depths generally increased after 20 d and decreased between 40 and 80 d. Electrical conductivity values gave the significant positive correlations with organic carbon, total N and NO3-N and a negative correlation with soil pH. The most increases in NO3-N and electrical conductivity values of all soil depths were obtained with tobacco wastes application. Leaching of decomposed materials along soil depth was greater with tobacco wastes application due to its fast mineralization.